'Running on sandcastles': energising the rhythmanalyst through non-representational ethnography of a running event. Issue 5 (3rd September 2019) - Larsen, Jonas
ABSTRACT: This article conducts an analysis that is informed by rhythmanalysis and non-representational ethnography of a five-day seasonal running event – Etape Bornholm – that takes place on the Danish holiday island of Bornholm during the summer school holiday. Firstly, I argue that rhythmanalysis in practice pays lip service to biological rhythms and is insufficiently corporeal, mobile or sensuous. In contrast, I energise the rhythmanalyst by outlining a perspective where the rhythmanalyst literally listens to his or her heartbeat and internal rhythms. I address this sensuous paucity in rhythm studies by connecting it with non/more-than-representational theories and ethnographies. Secondly, I advance landscape studies, sport geography and tourist studies by examining runners' bodily ways of practising and sensing landscapes during races. More broadly, this article contributes to ongoing debates in tourist studies on how tourists corporeally engage with and sense landscapes.